2014
DOI: 10.1016/j.drugalcdep.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Risks for early substance involvement associated with parental alcoholism and parental separation in an adolescent female cohort

Abstract: Background We examined timing of substance involvement as a joint function of parental history of alcoholism and parental separation during childhood. Method Data were drawn from a large cohort of female like-sex twins [n = 613 African Ancestry (AA), n = 3550 European or other Ancestry (EA)]. Cox proportional hazards regression was conducted predicting age at first use of alcohol, first alcohol intoxication, first use and regular use of cigarettes, and first use of cannabis and other illicit drugs from dummy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 45 publications
9
51
2
1
Order By: Relevance
“…First, logistic regression analyses were used to examine the association between low parental monitoring and early substance use without and with covariate adjustment. Next, consistent with earlier work (e.g., Waldron et al, 2014Waldron et al, , 2015, PSA was conducted to compare adolescents who reported low parental monitoring (lowest 25% within racial/ethnic group) and those who reported higher parental monitoring (upper 75%) based on their predicted probability of experiencing low parental monitoring. PSA is a statistical technique that can be used to reduce bias from confounding variables by matching groups on a range of highly correlated risk factors presumed to predate exposure (Green & Stuart, 2014;Rosenbaum, 2010;Rosenbaum & Rubin, 1983;West et al, 2014), in this case, to low parental monitoring.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, logistic regression analyses were used to examine the association between low parental monitoring and early substance use without and with covariate adjustment. Next, consistent with earlier work (e.g., Waldron et al, 2014Waldron et al, , 2015, PSA was conducted to compare adolescents who reported low parental monitoring (lowest 25% within racial/ethnic group) and those who reported higher parental monitoring (upper 75%) based on their predicted probability of experiencing low parental monitoring. PSA is a statistical technique that can be used to reduce bias from confounding variables by matching groups on a range of highly correlated risk factors presumed to predate exposure (Green & Stuart, 2014;Rosenbaum, 2010;Rosenbaum & Rubin, 1983;West et al, 2014), in this case, to low parental monitoring.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…PSA was developed to allow tests of causal hypotheses without dependence on strong linear statistical model assumptions, for situations where randomized experimentation was not possible. These methods have been successfully applied in prior research on early-onset substance use (e.g., Odgers et al, 2008;Waldron et al, 2014). In the current study, we used both logistic regression and PSA to control for the confounding effects of correlated background characteristics, the latter to confirm our confidence in the specific contribution of parental monitoring to early use of alcohol, tobacco, and cannabis.…”
mentioning
confidence: 99%
“…In research on children of alcoholics, there are a growing number of studies that model jointly risk from parental separation and parental alcoholism (e.g., Dube et al, 2002; Thompson et al, 2008, 2013; Waldron et al, 2014b). This includes a handful of genetically informative Offspring-of-Twins (OOT) analyses (Gottesman & Bertelsen, 1989; Heath et al, 1985; Nance & Corey, 1976), where genetic and environmental risks to offspring are inferred from twin-parent and co-twin histories of alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…To consider just one example, parental separation is a strong predictor of early-onset substance use, even after adjustment for parental substance use disorder histories (e.g., Waldron et al, 2014), and risk of parental separation is highly predictable from variables such as maternal age, educational level, and marital status at childbirth-all of which may be derived from the birth record. Do neighborhoods with increased rates of family separation predict increased rates of early-onset substance use, even after statistical control for other neighborhood risk indices and for individual and family-level variables?…”
Section: S With Other Complex (Non-mendelian)mentioning
confidence: 99%